The Reconstruction of Etymon Proto of Sambori and Teta Isolects Spoken in Bima Regency-NTB-Indonesia - I Gede Budasi (JURNAL ARBITRER, 2021)
The previous studies that describe the phonological system of the isolects and the description of their differing and uniting linguistic features have not yet answered the doubts among Indonesian linguists whether or not the Proto of Sambori-Teta (PSm-Te) were descended from Proto Austronesia (PAn). Thus, this article aims to describe the interrelatedness of the two protoes and to describe the types of sound changes from the PAn to PSm-Te etymons. This descriptive study applied a comparative method by implementing bottom-up and top-down analysis in reconstructing the PSm-Te. The linguistic features as the evidence of the interrelatedness of the two protoes were identified and analyzed using sound change theories. This study found 1691 (99.35%) definitive etymons of PSm-Te among 1702 etymons of Sambori and Teta Isolects identified in this study, and the types of sound change from PAn to PSm-Te etymons showed addition, deletion, metathesis, diphthongization, fusion, fortition, lenition, fronting, and backing. The definitive PSm-Te and the identified types of sound changes can be used as the linguistic evidence to determine that PAn descend PSm-Te. Therefore Sambori and Teta isolects reflect PSm-Te.